Bioassays for dioscorine in wild yam (Dioscorea hispida) processed using Bukidnon detoxifying procedure - Tolibas, Aissa V. (University of the Philippines, College of Home Economics, 2000)
ABSTRACT This study was done to document the dioscorine detoxification processing method for wild yam, Discorea hispida, harvested from Bukidnon. The Bukidnon detoxification processing method for wild yam was done by slicing th peeled tubers, soaking in 4-5% salt solution for 24h, washing with tap water for another 24 h, and sun-drying until crisp. Prior to consumption, the yam were boiled in water until cooked. Detoxified yams were recorded to cause only slight drowsiness to consumers. The toxicity changes in yam with the Bukidnon detoxification procedure were determined in the study using chick and fish bioassays. White Leghorn and Starbro chicks breed, and Poecilia latipinna fish were fed with boiled undetoxified yams. The fish assays was found not be an acceptable assay for dioscorine in the test food. Detoxified yam was not found to be toxic in the assayed chicks.However, undetoxified samples indicated clinical toxicity symptoms in chicks followed by an uneventful recovery by an average of 50% of the test animals. It also resulted death in about 20% of the tests chicks. A better assay than the fish and chick assyas used in the study must be considered to determine dioscorine toxicities in yam. Another recommendation is the adding of purification steps to extract the toxin from the yam and the use of another routes of administration of the toxin extracts to the test animals.